2017
DOI: 10.1002/2017jb014244
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Fluid Effect on Frequency‐Dependent Elastic Moduli in Fully Saturated Tight Sandstone

Abstract: We developed a system to explore the effects of pressure and fluid viscosity on the dispersion and attenuation of fully saturated tight sandstones, especially at seismic frequencies. Calibration of the new system revealed that the system can operate reliably at frequencies of [2–200, 106] Hz. Tight sandstone with a “crack–pore” microstructure was tested under nitrogen gas (dry), brine, and glycerin saturation. A frequency‐dependent effect was not found for the dry case. However, apparent dispersion and attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 64 publications
(106 reference statements)
2
46
0
Order By: Relevance
“…Thus, when comparing Gassmann's predictions with laboratory ultrasonic measurements, the effect of frequency on elastic moduli needs to be considered. That is why several laboratory facilities with a low-frequency measurement range have been developed during the past 40 years (Best et al, 2007;Fortin et al, 2014;Jackson, 2000;Jackson et al, 2011;Jackson & Paterson, 1993;Madonna & Tisato, 2013;McCarthy et al, 2011;Mikhaltsevitch et al, 2014;Murphy, 1985;Nakagawa et al, 2013;Peselnick & Liu, 1987;Saltiel et al, 2017;Spencer, 1981;Subramaniyan et al, 2014;Szewczyk et al, 2016;Tisato & Madonna, 2012;Wang et al, 2012;Yin et al, 2017). Murphy (1985) conducted laboratory measurements on granites using the resonant bar method at sonic frequency supplemented with the ultrasonic method and found that Gassmann's predictions worked better for low sonic frequency measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when comparing Gassmann's predictions with laboratory ultrasonic measurements, the effect of frequency on elastic moduli needs to be considered. That is why several laboratory facilities with a low-frequency measurement range have been developed during the past 40 years (Best et al, 2007;Fortin et al, 2014;Jackson, 2000;Jackson et al, 2011;Jackson & Paterson, 1993;Madonna & Tisato, 2013;McCarthy et al, 2011;Mikhaltsevitch et al, 2014;Murphy, 1985;Nakagawa et al, 2013;Peselnick & Liu, 1987;Saltiel et al, 2017;Spencer, 1981;Subramaniyan et al, 2014;Szewczyk et al, 2016;Tisato & Madonna, 2012;Wang et al, 2012;Yin et al, 2017). Murphy (1985) conducted laboratory measurements on granites using the resonant bar method at sonic frequency supplemented with the ultrasonic method and found that Gassmann's predictions worked better for low sonic frequency measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic properties of high‐ and intermediate‐porosity sandstones at different frequency ranges are relatively well investigated by many researchers (Batzle et al, 2006; Borgomano et al, 2017; Johnston et al, 1979; Mikhaltsevitch et al, 2014, 2016; Pimienta et al, 2017; Spencer & Shine, 2016; Yin et al, 2017). It is in general acknowledged that sandstones exhibit no significant dispersion and attenuation in dry conditions (Spencer, 1981; Winkler et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…For two fully saturated Fontainebueau sandstones with relatively low porosity, Pimienta et al (2015b) reported that there exist two strong attenuation peaks associated with drained/undrained and undrained/unrelaxed transitions. Yin et al (2017) recently performed the forced‐oscillation measurements over seismic frequencies from 2 to 200 Hz and concurrently at an ultrasonic frequency of 10 6 Hz for fully saturated tight sandstone. It is found that the squirt flow associated with crack–pore microstructure system in tight sandstone is mainly responsible for the dispersion of Young's modulus and extensional attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…In seismic exploration, the development of models to predict the characteristics of seismic waves in porous media is a considerable challenge. Through numerous experimental progress, the main characteristics of seismic waves are the velocity dispersions and amplitude attenuations, which can be observed in a broad range of frequencies in fluid-saturated porous media [5][6][7][8]. Several theories have been proposed to explain these phenomena at various scales [9].…”
Section: Introductionmentioning
confidence: 99%
“…The compliant pores are mainly cracks with small aspect ratios, and the intergranular pores are stiff with high aspect ratios. The porosities of these two types of pores can be measured under different pressures [8]. Similar to the mesoscopic heterogeneity mechanism, in the high-frequency regime, the fluid in the compliant pores is easily isolated by the stiff pores and the fluid pressure has no time to equilibrate.…”
Section: Introductionmentioning
confidence: 99%